Selective Gene Expression of Latent Murine Gammaherpesvirus 68 in B Lymphocytes - Marques, Sofia (American Society for Microbiology, 2003)
Intranasal infection of mice with murine gammaherpesvirus 68 (MHV-68), a virus genetically related to the human pathogen Kaposi's sarcoma-associated herpesvirus, results in a persistent, latent infection in the spleen and other lymphoid organs. Here, we have determined the frequency of virus infection in splenic dendritic cells, macrophages, and several B-cell subpopulations, and we quantified cell type-dependent virus transcription patterns. The frequencies of virus genome positive cells were maximal at 14 days postinfection in all splenic cell populations analyzed. Marginal zone and germinal center B cells harbored the highest frequency of infection and the former population accounted for approximately half the total number of infected B cells. Analysis of virus transcription during the establishment of latency revealed that virus gene expression in B cells was restricted and dependent on the differentiation stage of the B cell. Notably, transcription of ORF73 was detected in germinal center B cells, a finding in agreement with the predicted latent genome maintenance function of ORF73 in dividing cells. At late times after infection, virus DNA could only be detected in newly formed and germinal center B cells, which suggests that B cells play a critical role in facilitating life-long latency.